Community Partnership Program: Dissemination of Urban Farming Technology for Community of Jatinegara West Flats - Ahmad Rifqi Fauzi; Warid Warid; Maulidian Maulidian (Khadimul Ummah, 2019)
The world population population in 2050 is predicted to reach more than 9 billion and 66% of the population lives in urban areas. This can lead to competition in getting bigger food. Therefore, food security in urban areas is a big challenge. Mitigation to face the challenge has been done by city government in Indonesia. For example, the province of DKI Jakarta, where the provincial government has programmed to carry out urban farming activities as an effort to bring food sources near to the community as well as reforestation for the city. To support the program, Trilogy University through Community Partnership Program, since 2016, has disseminated the technology of urban agriculture and empowered the people residing in the area of West Jatinegara Flats, Jakarta. Methods of partnership activities include analysis of partner problems, interviews with partners, program socialization, trainning on cultivation techniques on smallholdings, and demonstrations of agricultural technology for urban areas. Activities that have been implemented are vertical farming training, composting, and community empowerment in the utilization of open land around the Flats. These activities have an impact, among others, people familiar with urban farming technology, lay out of open space utilization and hydroponics technology for net house of flats. This partnership program was established thanks to support from the Ministry of Technology and Higher Education Research and in collaboration with the Department of Maritime Agriculture and Food Security, DKI Jakarta Province.